Characterization and expression analysis of microRNAs in the tube foot of sea cucumber Apostichopus japonicus. - Hongdi Wang; Shikai Liu; Jun Cui; Chengze Li; Xuemei Qiu; Yaqing Chang; Zhanjiang Liu; Xiuli Wang (PLoS ONE, 2014)
MicroRNAs (miRNAs) are a class of endogenous non-coding small RNA with average length of 22 nucleotides, participating in the post-transcriptional regulation of gene expression. In this study, we report the identification and characterization of miRNAs in the tube foot of sea cucumber (Apostichopus japonicus) by next generation sequencing with Illumina HiSeq 2000 platform. Through the bioinformatic analysis, we identified 260 conserved miRNAs and six novel miRNAs from the tube foot small RNA transcriptome. Quantitative realtime PCR (qRT-PCR) was performed to characterize the specific expression in the tube foot. The results indicated that four miRNAs, including miR-29a, miR-29b, miR-2005 and miR-278-3p, were significantly up-regulated in the tube foot. The target genes of the four specifically expressed miRNAs were predicted in silico and validated by performing qRT-PCR. Gene ontology (GO) and KEGG pathway analyses with the target genes of these four miRNAs were conducted to further understand the regulatory function in the tube foot. This is the first study to profile the miRNA transcriptome of the tube foot in sea cucumber. This work will provide valuable genomic resources to understand the mechanisms of gene regulation in the tube foot, and will be useful to assist the molecular breeding in sea cucumber.